Penyembuhan Masalah Spiritual Pasien di Rumah Sakit Melalui Pendekatan Komunikasi Spiritual Terapeutik Berbasis Al-Qur'an - Mohamad Zaenal Arifin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Healing Spiritual Problems of Patients in Hospitals Through Al-Qur'an-Based Therapeutic Spiritual Communication ApproachThis study aims to investigate the use of therapeutic spiritual communication as an approach to healing patients' spiritual problems. In the suffering of his pain, the patient needs help recovering from spiritual problems that arise as a result of physical suffering. Researchers collected the primary data of this study from interviews with a number of nurses on duty at the University of Indonesia Hospital (RSUI), Depok. Data sources are critically analyzed to obtain complete information around the patient's spiritual problems, the application of therapeutic spiritual communication in spiritual nursing interventions, as well as the nurse's opinion about the dominant factors and obstacles encountered when assisting the healing process of the patient's problems. The results showed that the patient's spiritual problems were able to be overcome by nurses after carrying out therapeutic spiritual communication interventions in the form of; Awakening spiritual power in the patient by increasing the patient's self-confidence, instilling a sense of optimism, and confidence in being able to recover from pain, as well as increasing the sense of patience, ridho, hope, and depending on the strength of Allah Swt as a Healing Principle; Correcting and changing the wrong mindset that the patient has about pain suffering by taking it towards the point of view of the faith, such as: that pain pain is a form of Allah Swt's affection for the patient, the arrival of the disease is the decree of Allah Swt, He will not inflict anything beyond the ability of His servant, and there must be wisdom from the occurrence of pain experienced; Guiding patients to carry out worship activities that support recovery